Rotating machinery, optical methods & scanning LDV methods : proceedings of the 38th IMAC, a conference and exposition on structural dynamics 2020 /: proceedings of the 38th IMAC, a conference and exposition on structural dynamics 2020. (2020) - Unknown
No abstract available